1989
DOI: 10.1002/path.1711570104
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nerves and neuropeptides in skin from 100 leprosy patients investigated by immunocytochemistry

Abstract: The cutaneous innervation is now known to contain neuropeptides including substance P (SP) and calcitonin gene-related peptide (CGRP) in sensory nerves, and vasoactive intestinal polypeptide (VIP) and neuropeptide Y (NPY), principally in autonomic nerves. Skin biopsies from 100 leprosy patients and equivalent areas from 50 non-leprosy controls were fixed in p-benzoquinone solution for immunofluorescence staining and in Bouin's fluid for classification of leprosy type. Antisera to the neural markers, neurofilam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 38 publications
(2 reference statements)
2
29
0
Order By: Relevance
“…The antisera used to detect SP and CGRP have both previously been substantiated in other tissue, be ing used to delineate neuropeptide-containing nerves in the central nervous system [ 16], skin [ 17] and respir atory tract [18]. Within resected lung tissue, SP-im munoreactive nerves are difficult to detect or absent, a finding consistent with the reported findings of Ol lerenshaw et al [11,12] in non-asthmatic subjects.…”
Section: Discussionsupporting
confidence: 80%
“…The antisera used to detect SP and CGRP have both previously been substantiated in other tissue, be ing used to delineate neuropeptide-containing nerves in the central nervous system [ 16], skin [ 17] and respir atory tract [18]. Within resected lung tissue, SP-im munoreactive nerves are difficult to detect or absent, a finding consistent with the reported findings of Ol lerenshaw et al [11,12] in non-asthmatic subjects.…”
Section: Discussionsupporting
confidence: 80%
“…Immunohistochemical methods have been used to investigate cutaneous innervation changes in various dermatological diseases such as leprosy, systemic sclerosis, atopic dermatitis and psoriasis [18, 19, 20, 21]. Substance P is among the neuropeptides detected in sensory nerves of the skin and VIP is known to be present in cutaneous autonomic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed regarding the expression of PGP 9.5 (BB: p<0.001 and LL: p<0.05) and NF-L (LL: p<0.05), suggesting higher Remak bundles degeneration in multibacillary leprosy. Likewise, Karanth et al 29 observed impairment in PGP 9.5 and neurofilament immunoreactivity in leprosy lesions, mainly in tuberculoid patients. Moreover, the authors reported lack of neuropeptides in most of leprosy lesions.…”
Section: Discussionmentioning
confidence: 90%